Cost-effective, scalable production of glucose oxidase using Casuarina equisetifolia biomass and its application in the bio-Fenton oxidation process for the removal of trace organic contaminants from wastewater. (June 2023) - Vaidyanathan, Vinoth Kumar; Alanazi, Abdullah K.; Senthil Kumar, P.; Rajendran, Devi Sri; Chidambaram, Ashok; Venkataraman, Swethaa; Kumar, Vaithyanathan Vasanth; Rangasamy, Gayathri; Cabana, Hubert; Abo-Dief, Hala M.
Graphical abstract: Highlights: Casuarina equisetifolia biomass was used for production of glucose oxidase. Pilot scale glucose oxidase production from Aspergillus niger was demonstrated. 602 U/mL of glucose oxidase (GOD) was produced after 96 h of fermentation time. 544.3 mg/L of GOD assisted H2 O2  production was optimized by RSM. GOD-driven H2 O2  was used in bio-Fenton process removed 36–89% of TrOCs. Abstract: This study focuses on using Casuarina equisetifolia biomass for pilot-scale glucose oxidase production from Aspergillus niger and its application in the removal of trace organic contaminants (TrOCs) from municipal wastewater through the bio-Fenton oxidation. The cost of glucose oxidase was 0.005 $/U, including the optimum production parameters, 10% biomass, 7% sucrose, 1% peptone, and 3% CaCO3 at 96 h with an enzyme activity of 670 U/mL. Optimized conditions for H2 O2 were 1 M glucose, 100 U/mL glucose oxidase, and 120 mins of incubation, resulting in 544.3 mg/L H2 O2 . Thus, H2 O2 produced under these conditions lead to bio-Fenton oxidation resulting in the removal of 36–92% of nine TrOCs in municipal wastewater at pH 7.0 in 360 mins. Therefore, this work establishes the cost-effective glucose oxidase-producing H2 O2 as an attractive bioremediating agent to enhance the removal of TrOCs in wastewater at neutral pH.